2013
DOI: 10.5012/bkcs.2013.34.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity, Dielectric Behavior and EMI Shielding Effectiveness of Polyaniline-Yttrium Oxide Composites

Abstract: Polyaniline-yttrium trioxide (PAni-Y 2 O 3 ) composites were synthesized by the in-situ polymerization of aniline in the presence of Y 2 O 3 . The composite formation and structural changes in these composites were investigated by X-ray diffraction (XRD), Fourier transform infra red spectroscopy (FTIR), scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). The direct current (DC) electrical conductivity of the order of 0.51 × 10 −2 S cm −1 -0.283 S cm −1 in the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Using non‐magnetic and electrically insulating fly‐ash filler particles, Singh et al, observed an SE value of ∼ ‐32 dB (for 33 wt% PANI and 67 wt% fly‐ash). Furthermore, Faisal et al observed the effect of percolation of Y 2 O 3 (dielectric) particles in PANI‐matrix. They found that, at the percolation threshold (20 wt % of Y 2 O 3 ), the dielectric constant and dielectric loss are maximum.…”
Section: Resultsmentioning
confidence: 99%
“…Using non‐magnetic and electrically insulating fly‐ash filler particles, Singh et al, observed an SE value of ∼ ‐32 dB (for 33 wt% PANI and 67 wt% fly‐ash). Furthermore, Faisal et al observed the effect of percolation of Y 2 O 3 (dielectric) particles in PANI‐matrix. They found that, at the percolation threshold (20 wt % of Y 2 O 3 ), the dielectric constant and dielectric loss are maximum.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are no studies on EMI shielding properties of dielectric polymer composites (PEK/BT composites) but lot of research has been carried out to understand EMI shielding performance of conducting polymer composites (CPCs). Faisal and Khasim studied the effect of different inorganic oxide fillers like yttrium oxide (Y 2 O 3 ), stannous oxide (SnO), antimony oxide (Sb 2 O 3 ) on EMI shielding behavior of polyaniline. EMISE of PAni/Y 2 O 3 composites in the frequency range 100 Hz to 2 GHz was in the range of −12.2 to −17.2 dB with highest value of ∼–17 dB at 20 wt % loading which is sufficient for many practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies related to the development of electromagnetic shielding materials have become increasingly popular. [8][9][10][11][12][13] EMI shielding is concerned with protecting devices or humans from electromagnetic waves by reducing the harmful waves present around the protection targets. For this purpose, either the unnecessary electromagnetic waves are shielded, or new circuits are formed using magnetic bodies or conductors.…”
Section: Introductionmentioning
confidence: 99%